Pengaruh Audit Tenure, Audit Delay, Opini Audit Tahun Sebelumnya dan Opinion Shopping Terhadap Penerimaan Opini Audit Going Concern Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2015 - Syahputra, Fauzan; Yahya, M Rizal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The Purpose of this research is to know the influence of audit tenure, audit delay, prior opinion, and opinion shopping to the going concern opinion at manufacturing companies registered in BEI with simultaneously as well as partial relation. The population is manufacturing company listed in BEI in 2013 to 2015 with sample method used that is Purposive Sampling. Analytical techniques used in this research is analysis of logistic regression. The results of this research are partially variable there are audit tenure and opinion shopping are affect the going concern opinion. Variable audit delay and prior opinion have no effect on the going concern opinion. While in the simultaneously relation, the entire research was influential variables are significantly to the going concern opinion.